Managing school discipline and implications for school social workers: A review of the literature - Cameron, M. (Children and Schools, 2006)
School disciplinary policies and practices are essential features of life in U.S. schools. Conventional approaches to school discipline - including conduct codes and security methods, suspension, corporal punishment, and teachers' methods of managing student behaviors - rely primarily on deterrence, control, and punishment to maintain order. However, approximately 40 years of research, chiefly in education and psychology, has demonstrated that these policies and practices are often associated with and can contribute to increased disorder in schools and behavioral and academic problems among students. Furthermore, school discipline is sometimes administered prejudicially to those students who may be the most vulnerable. School social workers and all social workers working with children and youths can help schools adopt effective and nonpunitive disciplinary approaches. Key professional actions include advocacy for schoolchildren subject to unfair and overly punitive discipline; educating teachers and administrators about the potential harm associated with conventional disciplinary practices; educating school personnel about effective, nonpunitive approaches; and creating a public campaign to generate popular support for the reform of iatrogenic school disciplinary practices. © 2006 National Association of Social Workers.
Keywords: Children; Discipline; Punishment; School social work; Schools; dept.swk

School discipline and social work practice: Application of research and theory to intervention - Cameron, M.; Sheppard, S.M. (Children and Schools, 2006)
Research has identified a relationship between school disciplinary actions and poor academic and psychosocial functioning of students subjected to them. The ways in which school discipline is a direct contributor to students' academic and psychosocial difficulty needs to be further established empirically. Several theories, based in existing research and theory in sociology of education and educational psychology, have been proposed to explain the school discipline - student dysfunction relationship. They generally suggest three pathways: disciplinary actions may contribute to students' psychological problems; student misbehavior may be encouraged through ineffective and unintentionally paradoxical learning experiences; and disciplinary practices may damage students' relationship with school. School social workers and others working with children who have been disciplined at school can use these research findings and theories as an assessment framework to guide their interventions.The awareness of the iatrogenic potential of school discipline and informed assessment can support a range of evidence-based alternatives to school discipline. © 2006 National Association of Social Workers.
Keywords: Assessment; Children; Discipline; School social work; Schools; dept.swk

Assertive outreach: An effective strategy for engaging homeless persons with substance use disorders into treatment - Fisk, Deborah; Rakfeldt, Jaak; McCormack, Erin (American Journal of Drug and Alcohol Abuse, 2006)
The purpose of this study was to examine substance abuse treatment referrals that were made by outreach workers in a homeless outreach project. Ten outreach workers completed questionnaires on each of their clients who they had referred to a substance abuse treatment program over the previous year. Additional data was collected on the client's motivation level at the point the referral was made, which agencies the client was referred to, and if the client was rejected from any of the treatment programs. Bivariate correlation analyses were used to examine relationships between the variables. Of 73 project clients who were referred to substance abuse treatment in a one-year period of time, 41% successfully entered treatment. As might be expected, there was a statistically significant relationship between clients' motivation level and completed referral, and between referrals made and program acceptance. This study provides evidence that assertive outreach is effective in engaging and linking homeless persons with substance use disorders to substance abuse treatment services.
Keywords: Adolescent; Adult; Assertive outreach; Community-Institutional Relations; Female; Homeless Persons; Homeless populations; Humans; Male; Middle Aged; Substance abuse; Substance-Related Disorders; Treatment Outcome; adult; article; assertiveness; correlation analysis; dept.swk; drug dependence treatment; female; homelessness; human; major clinical study; male; mental health service; motivation; patient referral; social work; social worker; statistical significance; substance abuse